Type and approach of hysterectomy and oncological survival of women with stage II cancer of endometrium: a large retrospective cohort study - Shuai, Xu; Xiao, Dan; Han, Binhua; Du, Yixue (Frontiers in Oncology, 2024)
To explore the association between the Type and approach of hysterectomy and oncological survival of women with stage Ⅱ cancer of the endometrium684 women with stage Ⅱ endometrial cancer were included. Eligible cases were grouped by type of hysterectomy (simple hysterectomy or radical hysterectomy)and approach of hysterectomy (laparoscopy or laparotomy). The baseline characteristics were compared among groups. The survival outcomes (disease-free survival and overall survival) were calculated and compared among groups, and the underlying confounding factors were adjusted by the Cox proportional hazard regression analysis.The radical hysterectomy group and the simple hysterectomy group had 217 cases and 467 cases, respectively. Between the groups, the difference in 5-year disease-free survival (87.3% versus 87.9%, HR=0.97, P=0.87) and 5-year overall survival (83.8% versus 83.8%, HR=0.95, P=0.95) was not statistically significant. The laparotomy group and the laparoscopy group had 277 cases and 407 cases, respectively. Between the groups, the difference in 5-year disease-free survival (88.7% versus 87.1%, HR=1.22, P=0.34) and 5-year overall survival (85.5% versus 82.7%, HR=1.00, P=0.99)was not statistically significant.For long-term oncological survival, radical hysterectomy is not superior to total hysterectomy in stage Ⅱ endometrial cancer. Also, for stage Ⅱ cancer of the endometrium, laparoscopic hysterectomy is as oncologically safe as open hysterectomy.